DISPUTE SETTLEMENT ON THE OWNERSHIP OF TRADEMARK WITH SIMILARITY (CASE STUDY BETWEEN GUDANG GARAM VS GUDANG BARU) - Selly Marcelina; Sujana Donandi S (President University, 2017)
One of the difficulties arising from the provisions of Law no. 15 of 2001 regarding trademark is the lack of clear guidelines to determine the criteria of a well-known and famous trademark. One of the disputes on a famous trademark was between Gudang Garam and Gudang Baru that has been settled by the Supreme Court through decision No. 162 K /Pdt.Sus-HKI/2014. Problems in this research are regarding the Legal Consequences of the Verdict of the Supreme Court Number 162 K / Pdt.Sus-Hki / 2014 and how to determine the ownership of Trademark with Similarity. The methodology of this research is normative-empirical which is the combination of normative and empirical legal research. The results show that The verdict of Supreme Court Number 162 K/ Pdt.Sus-Hki/2014 determined that as long as a trademark has been registered in Indonesia, the trademark will be given a legal protection even though the trademark has similarity with other trademark that has been famous in many other countries. This verdict is not coherence with indonesian trademark law that does not admit trademark upon a trademark with similarity. The criteria of the determination of the equation basic elements in a famous brand that is the similarity of images, phenotic, names, words, letters, numbers, color arrangement or combination of such elements.